Grandma’s Recipes: Adding Value to Chili Paste Products, Den Pa Sak Community Housewives Group, Chiang Rai Province - Watthanasirisat, Natthiya (Area Based Development Research Journal, 2022)
Den Pa Sak Community Housewives Group, Mae Chan district, Chiang Rai Province, produces chili paste for sale, but the packaging required a more pleasing label to attract customers. The research objectives are to develop the package and add value to Chili Paste products from community enterprises that are cultural heritage. The research process involves in-depth interviews and focus-group meetings with four product design experts. Participants consist of one researcher, two community leaders, and ten members of the homemaker group. The processes include 1) product development, 2) distribution channel, and 3) logo and packaging implementations. The outcomes are the product branded “GRANDMA’S RECIPES”, its logo showing the community's and the group's identity, and the product labels. The new packaging is different in packing style, size, and shape. The product developed as a souvenir is in sturdy, not easily breakable packaging that allows a longer shelf life. In conclusion, the product is more recognizable, and as more customers buy the chili paste products of Den Pa Sak Community Housewives group, the average monthly sales increases from 34,800 Baht to 37,750 Baht.